2018
DOI: 10.1029/2018gl078088
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Disturbances Triggered by SpaceX Falcon Heavy

Abstract: SpaceX launched its Falcon Heavy demonstration mission at 20:45 UT on 6 February 2018 at NASA Kennedy Space Center in Florida. Short‐period northward propagating traveling ionospheric disturbances (TIDs) were observed following the shock waves in the ionospheric total electron content over East Florida‐Atlantic region. These TIDs have the periods of ~6–8 min, amplitude of ~0.05 total electron content unit, horizontal phase velocities of ~420–488 m/s, and horizontal wavelengths of ~164–240 km. They lasted for ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
(72 reference statements)
1
18
0
Order By: Relevance
“…In equinox (winter) when the sunrise terminator is orientated meridionally (more eastward), the westward magnetic declination at MH causes later sunrise in the E‐region than F‐region on the same field line, which helps sustain PEFs. Furthermore, the observed TID wavefronts with a meridional alignment in the early morning seems necessary to maintain the PEFs, as extensively discussed previously (Chou et al., 2018; Krall et al., 2013; Tsunoda, 2010; Varney et al., 2009).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In equinox (winter) when the sunrise terminator is orientated meridionally (more eastward), the westward magnetic declination at MH causes later sunrise in the E‐region than F‐region on the same field line, which helps sustain PEFs. Furthermore, the observed TID wavefronts with a meridional alignment in the early morning seems necessary to maintain the PEFs, as extensively discussed previously (Chou et al., 2018; Krall et al., 2013; Tsunoda, 2010; Varney et al., 2009).…”
Section: Discussionsupporting
confidence: 65%
“…Under this scenario, ST associated TIDs are electrified, although GWs remain fundamental in initiating such PEFs and driving plasma disturbance propagation along with GWs. Along these lines, previous studies have indicated that the GW wind dynamo action can induce PEFs, particularly when the wavefronts are aligned in the meridional/magnetic field direction (e.g., Chou et al, 2018;Krall et al, 2013;Huba et al, 2015;Hysell et al, 2018;Tsunoda, 2010). In another example, Varney et al (2009) presented Jicamarca incoherent scatter radar (ISR) observations of nighttime electric fields generated by GWs whose propagation vectors were nearly perpendicular to the magnetic meridian.…”
mentioning
confidence: 96%
“…There are explosive events that created a broad spectrum of perturbations in both acoustic and gravity wave modes, for example, rocket launches that produce shock‐acoustic waves followed by concentric gravity waves (Lin, Shen, et al., 2017) or thermospheric ducted gravity waves (M.‐Y. Chou et al., 2018). An extreme case is the 2011 Tohoku earthquake and tsunami, which triggered diverse spectra of TIDs with phase velocities of ∼3.5 km/s (Rayleigh wave), 1–1.2 km/s (acoustic wave), ∼300–590 m/s (gravity wave), and ∼200–250 m/s (tsunami wave) (e.g., Azeem et al., 2017; Chen et al., 2011; M.‐Y.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the gravity wave wind‐driven dynamo paradigm appears to be the most plausible mechanism to explain the conjugate MSTIDs (Chou, Lin, Shen, et al., 2018; Huba et al., 2015). Huba et al.…”
Section: Discussionmentioning
confidence: 99%